Molecular Mechanisms of Iron Mediated Programmed Cell Death and Its Roles in Eye Diseases - Zhang, Jie; Sheng, Shuai; Wang, Wenting; Dai, Jiazhen; Zhong, Yifan; Ren, Jiantao; Jiang, Keke; Li, Shuchan; Bian, Xiaoyan; Liu, Lei (Frontiers in Nutrition, 2022)
Ferroptosis, a newly identified, iron-dependent type of programmed cell death, is active in several diseases, such as heart disease, brain damage, and cancer. Its main characteristics commonly involve excess iron accumulation, elevated lipid peroxides and reactive oxygen species, and reduced levels of glutathione and glutathione peroxidase 4 levels. The effects of ferroptosis in eye diseases cannot be underestimated, with ferroptosis becoming a research target in ocular disorders and emerging evidence from a series of in vivo and in vitro researches into ferroptosis revealing its role in eye conditions. However, no report provides comprehensive information on the pathophysiology of ferroptosis in eye diseases and its possible treatments. In the current review, we present an up-to-date overview of ferroptosis biology and its involvement in the pathological processes of ocular diseases. Furthermore, we pose several outstanding questions and areas for future research in this topic. We deem ferroptosis-associated cell death a pivotal new field of scientific study in ocular diseases and consider it a new therapeutic target in the treatment of some eye disorders.